Criminal conduct: Theories with psychological input and research perspectives - Pomahuacre Carhuayal, Juan Walter (2017)
In this article, an analysis of the criminal behavior is made, relating these to the most current criminological theories. It describes its psychological aspects and its influence in the development of criminal behavior, individual or grupal. It then shows how research supports these theoretical formulations. It is advisable to use qualitative research to generate contextual explanations. About this, narrative designs are emphasized, because they allow criminals to reflect on their own lives through their own words, and for researcher, a genuine social, ethical and political personal commitment.